Landscape as Urban Regeneration: Learning from The High Line & Seoullo 7017 Skypark - Romi Bramantyo Margono; Siswanti Zuraida (JOURNAL OF APPLIED SCIENCE (JAPPS), 2019)
Industrial Revolution has a significant contribution to forming the global cities. Many developments happened dictated by Industrial needs simultaneously with increasing number of populations by urbanization. One part of development to support industrialization and urbanization is infrastructures. Infrastructures such as street for cars and train railway. The development of infrastructures is affecting health, social, economic, and environment of citizen. It is also responsible for the decline of quality of life in many global cities. As time goes by, another significant shift happens in many global cities. Infrastructure becomes outdated, industry leaves, the local economy deflates, residents flee and the community implodes. It leaves many derelict infrastructures, other facilities of industry, and diverse impacts. To tackle this situation, Urban Regeneration concept was introduced. Furthermore, landscape also can be used as a tool of urban regeneration concept that intended to improve quality of life in the cities. According to this situation, there are two projects that represent landscape project as urban regeneration. The first project is The Highline project in New York by James Corner Field Operations, Diller Scofidio + Renfro, and Piet Oudolf that revitalizing previous railway and Seoullo 7017 Skygarden in South Korea by MVRDV that revitalizing previous highway. The aim of this paper are to presents more insight and elaboration about how urban regeneration implemented in the cities from two landscape projects example and describe some critical review of both projects.